On the History of Agriculture in the South Province of Dalmatia (The Examples from the East Coast of Adriatic Sea and its Surrounding Areas) - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The paper presents data on agricultural areas and the specific plant breeding in the south province of Dalmatia in the ancient times. Written authentic sources and archeological findings from this area point out to the tradition of planting and breeding from the Roman period till today. It is presumed that agriculture even during the Roman rule was the main activity of local people in the area, which is true even today. Besides agriculture, animal husbandry was highly significant activity as well. Oral sources emphasize that, in the south province of Dalmatia, agriculture was primarily based on breeding specific plants such as barley, millet, oats, carrots, and turnip in the ancient times as well as today. Certain material remains that testify to the agricultural activities of that time were found in the south province of Dalmatia and its surrounding areas. These remains are historically highly valuable because they present the economic circumstances and the history of agriculture from the ancient times till today in more details. Even though ancient writers and archeological findings do not provide enough data to learn more about agriculture in the ancient times in the south province of Dalmatia, it is considered that the use of agro-technic tools (plough, two-field system) with the arrival of the Romans improved the conditions for animal husbandry generally and in the south province of Dalmatia as well.
Keywords: tradition; agriculture; the Roman agricultural estates (fundi); agricultural products; Illyria; Dalmatia